2016
DOI: 10.1155/2016/5697571
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Scutellaria baicalensis for the Treatment of Hand, Foot, and Mouth Disease Associated with Encephalitis in Patients Infected with EV71: A Multicenter, Retrospective Analysis

Abstract: This study aimed to evaluate the clinical efficacy and safety of using the traditional Chinese herbal medicine Scutellaria baicalensis for the treatment of severe HFMD in 725 patients aged >1 year in a multicenter, retrospective analysis. The patients were divided into the S. baicalensis and ribavirin groups, and the temperatures, presence or absence of skin rashes and oral lesions, nervous system (NS) involvement, and viral loads of the patients, as well as the safety of the treatments, were evaluated. The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Recently, Lin et al. (2016) reported that S. baicalensis could be used to treat severe HFMD (Hand, Foot, and Mouth Disease) in patients aged >1 year, rapidly relieving fever, attenuating oral lesions and rashes, and improving nervous system involvement. This result was derived from a multi-center and retrospective analysis (Lin et al.…”
Section: Pharmacological Activities Of Extracts and Major Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Lin et al. (2016) reported that S. baicalensis could be used to treat severe HFMD (Hand, Foot, and Mouth Disease) in patients aged >1 year, rapidly relieving fever, attenuating oral lesions and rashes, and improving nervous system involvement. This result was derived from a multi-center and retrospective analysis (Lin et al.…”
Section: Pharmacological Activities Of Extracts and Major Compoundsmentioning
confidence: 99%
“…This result was derived from a multi-center and retrospective analysis (Lin et al. 2016). It is reasonable to assume that S. baicalensis and its compounds possess a common, non-specific anti-viral mechanism, based on its inhibitory effects on different types of viruses.…”
Section: Pharmacological Activities Of Extracts and Major Compoundsmentioning
confidence: 99%
“…In recent years, many publications have demonstrated the antiviral effects of some plant extracts . However, except for hand, foot, and mouth disease caused by enterovirus 71, very few studies have evaluated the effects of plant extracts against enteroviruses . In People's Republic of Congo and other countries in Africa, traditional practitioners commonly use plant crude extracts to treat various undiagnosed diseases in patients with symptoms that can be seen in the course of enterovirus infections.…”
Section: Introductionmentioning
confidence: 99%
“…Due to a successful clinical trial, it is now listed officially in the 2020 Chinese Pharmacopoeia, 2020 British Pharmacopoeia, and European Pharmacopoeia v10.0. Huangqin's major chemical constituents are flavonoids, which contribute to its therapeutic effects, including anti-viral ( Lin et al, 2016 ), lung injury ( Yang et al, 2019a ), hepatoprotective ( Yang et al, 2019a ), and neuroprotective activities ( Li et al, 2019 ). A total of 100 flavonoids (56 free flavonoids and 44 flavonoid glycosides) have been isolated from Scutellaria baicalensis ( Wang et al, 2018 ), among which baicalein, baicalin, wogonin, and wogonoside ( Fig.…”
Section: Promising Crude Extracts From Chinese Herbal Medicines For Tmentioning
confidence: 99%